New species of the genus Colobostema Enderlein (Diptera: Scatopsidae) from Mexico - Huerta, Heron (Zootaxa, 2013)
Five new species of the genus Colobostema Enderlein, 1926 from Mexico are described and illustrated: C. emilianoi (Chiapas), C. marielae (San Luis Potosi), C. valentinae (Jalisco), C. lupitae (Oaxaca) and C. marlettae (Yucatan). A key to the males of Neotropical species of Colobostema is provided. The male genitalia structures (especially the vestiture of parameres and the shape of tergite 9) indicates that all these new species form a group of closely related taxa, associated to the species of the Nearctic and Neotropical region.